The Effect of Workplace Counseling on ASN Performance Through Work Engagement as a Mediating Variable - Tiara Giani Putri; Osly Usman (Journal of Digital Business and Global Economy, 2026)
This study takes State Civil Servants (ASN) of the Ministry of Home Affairs of the Republic of Indonesia as its research subjects and aims to verify the impact of workplace counseling on ASN’s job performance, as well as the mediating role of work engagement. It adopts a quantitative explanatory research design, using 50 ASN who participated in the 2025 Counseling Week program as the study sample. Data was collected via Likert-scale questionnaires and analyzed using the partial least squares structural equation modeling tool available in SmartPLS software. The β values and p-values of all four tested effects all met the required standards, confirming that work engagement functions as a partial mediating variable. Based on these results, this study recommends that all types of institutions institutionalize workplace counseling programs and integrate them into their civil service capacity development strategies.